An Introduction to Formal Languages and Automata
Written to address the fundamentals of formal languages, automata, and computability, An Introduction to Formal Languages and Automata, Fifth Edition, provides an accessible, student-friendly presentation of all the material essential to an introductory Theory of Computation course. It is designed to familiarize students with the foundations and principles of computer science and to strengthen the students? ability to carry out formal and rigorous mathematical arguments. In the new Fifth Edition, Peter Linz continues to offer a straightforward, uncomplicated treatment of formal languages and automata and avoids excessive mathematical detail so that students may focus on and understand the underlying principles. The new edition also features a close connection between the text and JFLAP, which lets students follow difficult constructions and examples step-by-step, thus increasing understanding and insight.